The preparatory state of ground reaction forces in defending against a dribbler in a basketball 1-on-1 dribble subphase - Fujii, K.; Yoshioka, S.; Isaka, T.; Kouzaki, M. (Sports Biomechanics, 2015)
We previously demonstrated the relationship between sidestepping performance and the preparatory state of ground reaction forces (GRFs). The present study investigated the effect of the preparatory state of GRFs on defensive performance in 1-on-1 subphase of basketball. Ten basketball players participated in 1-on-1 dribble game of basketball. The outcomes (penetrating and guarding) and the preparatory state of GRFs (non-weighted and weighted states, i.e. vertical GRFs below and above 120% of body weight, respectively) were assessed by separating the phases. In the non-weighted state and the weighted state to determine the outcome, the probability of successful guarding was 78.8% and 29.6%, respectively. The non-weighted state prevented delay of the defensive step in the determination phase. Both the non-weighted and weighted states, immediately before the determination phase, were likely to change to the weighted state in the determination phase; during this time, the defender's preparatory state would be destabilised, presumably by the dribbler's movement. These results revealed that the preparatory GRFs before the defensive step help to explain the outcome of the 1-on-1 subphase, and suggest a better way to prevent delaying initiation of the defensive step and thereby to guard more effectively against a dribbler.